Blockade of Alternative Complement Pathway in Dense Deposit Disease. (6th February 2014) - Berthe-Aucejo, Aurore; Sacquépée, Mathieu; Fila, Marc; Peuchmaur, Michel; Perrier-Cornet, Emilia; Frémeaux-Bacchi, Véronique; Deschênes, Georges
Abstract : A patient aged 17 with dense deposit disease associated with complement activation, circulating C3 Nef, and Factor H mutation presented with nephrotic syndrome and hypertension. Steroid therapy, plasma exchange, and rituximab failed to improve proteinuria and hypertension despite a normalization of the circulating sC5b9 complex. Eculizumab, a monoclonal antibody directed against C5, was used to block the terminal product of the complement cascade. The dose was adapted to achieve a CH50 below 10%, but proteinuria and blood pressure were not improved after 3 months of treatment.